Multicomponent Synthesis of N-Heterocycles in Natural Deep Eutectic Solvents (NADES): A Critical Review - Daroon Raffik (Indonesian Journal Publisher, 2025)
Green solvents are intended to provide more sustainable alternatives in chemical synthesis, yet they often come with a trade-off in reaction efficiency. Natural Deep Eutectic Solvents (NADES) have recently attracted significant interest due to their intrinsic advantages-namely, biocompatibility, low toxicity, and readiness to biocompatibility, low toxicity, and readiness to biocompatibility, low toxicity, and readiness to biodegrade. Despite these benefits, several practical limitations remain, including their notably high viscosities (50-10,000 cP) , susceptibility to thermal degradation above 80°C , and compositional changes that occur during recycling, all of which restrict their broader applicability. This review critically examines the progress made from (2025 to 2025) in using NADES as a mediator for multicomponent reactions (MCRs) leading to nitrogen- based heterocyclic rings. Using rigorous inclusion criteria relevant to NADES- assisted MCRs within the specified timeframe, a total of 127 articles were found through systematic searches of Web of Science, Scopus, and PubMed. Many NADES- mediated transformations demonstrated remarkable efficiencies throughout these investigations; several reports indicated yields of 85 – 98 % and substantial increases in E- factor values of 40 – 70 % . The environmental benefits are somewhat offest by higher energy requirements, primarily because some protocols require higher temperatures and longer reaction times. NADES technology is still a feasible alternative to the conventional hazardous flow synthesis technique , and its promise is especially pertinent to sectors that largely depend on heterocyclic scaffolds, like fine chemicals, agrochemicals, and medicines. Moving forward, research should prioritize the development of task- specific NADES, optimization of reaction conditions for scale-up, and the establishment of standardized experimental procedures to enhance reproducibility across different laboratories. In addition to identifying important research gaps that need to be filled, this study advances the field by offering a fundamental framework for assessing (NADES) performance in industrial settings and setting reasonable standards for upcoming advancements in sustainable synthetic techniques.